Day-to-day variability of toxic events induced by organic compounds bound to size segregated atmospheric aerosol. (July 2015) - Topinka, Jan; Rossner, Pavel; Milcová, Alena; Schmuczerová, Jana; Pěnčíková, Kateřina; Rossnerová, Andrea; Ambrož, Antonín; Štolcpartová, Jitka; Bendl, Jan; Hovorka, Jan; Machala, Miroslav
Abstract: This study quantified the temporal variability of concentration of carcinogenic polycyclic aromatic hydrocarbons (c-PAHs), genotoxicity, oxidative DNA damage and dioxin-like activity of the extractable organic matter (EOM) of atmospheric aerosol particles of aerodynamic diameter (dae, μm) coarse (1 < dae < 10), upper- (0.5 < dae < 1) and lower-accumulation (0.17 < dae < 0.5) and ultrafine (<0.17) fractions. The upper accumulation fraction formed most of the aerosol mass for 22 of the 26 study days and contained ∼44% of total c-PAHs, while the ultrafine fraction contained only ∼11%. DNA adduct levels suggested a crucial contribution of c-PAHs bound to the upper accumulation fraction. The dioxin-like activity was also driven primarily by c-PAH concentrations. In contrast, oxidative DNA damage was not related to c-PAHs, as a negative correlation with c-PAHs was observed. These results suggest that genotoxicity and dioxin-like activity are the major toxic effects of organic compounds bound to size segregated aerosol, while oxidative DNA damage is not induced by EOM. Highlights: The day-to-day variability of the toxicity of organic extracts from PM was studied. Genotoxicity and dioxin-like activity are the main effects of compounds bound to PM. Upper accumulation mode exhibited highest genotoxicity and dioxin-like activity. Oxidative DNA damage is not induced by c-PAHs and other extract components. Abstract : The results suggest that genotoxicity and dioxin-like activity are the major toxic effects of organic compounds bound to size segregated aerosol, while oxidative damage is not induced.